Odpowiedzi

2009-12-07T19:49:32+01:00
Najlepsza Odpowiedź!
2009-12-07T19:51:16+01:00
A) (x+4)+(2x-6)=x+4+2x-6=3x-2
b) -(2y+3x)+(-4y+2x+1)=-2y-3x-4y+2x+1=-6y-x+1
c) -(x-2xy)-(4x+xy)+(xy-x)=-x+2xy-4x-xy+xy-x=-6x+2xy
d) (x²+2x+1)-(x²-4x+3)=x²+2x+1-x²+4x-3=6x-2
2009-12-07T19:51:53+01:00
A) (x+4)+(2x-6)= x + 4 + 2x - 6 = 3x -2

b) -(2y+3x)+(-4y+2x+1)= -2y - 3x - 4y + 2x + 1 = -6y + x + 1

c) -(x-2xy)-(4x+xy)+(xy-x)= -x + 2xy - 4x - xy + xy - x = -6x + 2xy

d) (x²+2x+1)-(x²-4x+3)= x² + 2x + 1 - x² + 4x - 3 = 6x -2